Future experiments using forward electron spectroscopy to study the quantum dynamics of high-Zions at the ESR/CRYRING storage rings - Hillenbrand, Pierre-Michel; Hagmann, S.; Stöhlker, Th; Litvinov, Yu; Kozhuharov, C.; Spillmann, U.; Shabaev, V.; Stiebing, K.; Lestinsky, M.; Surzhykov, Andrey; Voitkiv, A.; Franzke, B.; et al. (Physica scripta, 2013)
At the FAIR facility for antiproton and ion research, the new ESR + CRYRING combination of storage rings CRYRINGESR opens up a wealth of opportunities for in-ring atomic physics experiments on few-body quantum dynamics. The low-energy storage ring CRYRING will serve in its new location at FAIR/ESR for experiments with decelerated antiprotons and highly charged ions. We will discuss selected new experiments in the field of quantum dynamics of high-Z ions, for example for adiabatic superheavy quasi-molecules transiently formed with bare and H-like projectiles. Such experiments will be for the first time possible at the future CRYRING at ESR.
Gesehen am 11.05.2021